South Africa Sues International Court Over Israel's Palestinian Genocide under International Law - M. Fabian Akbar; Manuel Beltrán Genovés (Lampung Journal of International Law)
This article examines the legal and geopolitical implications of South Africa's unprecedented lawsuit against Israel for genocide in Gaza, brought before the International Court of Justice (ICJ). The conflict stems from longstanding tensions between Israel and Palestine, exacerbated during the October 7, 2023 crisis. South Africa's legal action alleges Israel's actions and omissions in Gaza constitute genocide under the 1948 Genocide Convention, citing evidence of extensive civilian casualties, particularly women and children. Israel, however, denies the accusations, attributing civilian deaths to Hamas and asserting its right to self-defense against rocket attacks. The ICJ's role as a peaceful dispute resolution forum is highlighted, emphasizing its authority to adjudicate disputes between nations and provide legal opinions. The research employs a normative legal approach, analyzing international law principles and regulations, using a case study methodology to explore the legal complexities of the case qualitatively. The findings contribute to a deeper understanding of the legal mechanisms governing international disputes and the potential impact of legal proceedings on conflict dynamics.